1993
DOI: 10.1017/s0950268800068230
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities and serotyping of Neisseria gonorrhoeae in southern Africa: influence of geographical source of infection

Abstract: SUMMARYOne hundred and ninety-two strains of Neisseria gonorrhoeae isolated from migrant mine-workers were tested for their susceptibility to antibiotics, auxotyped and serotyped. Of the total, 93 (48%) were acquired locally and 64 (33%) from different geographical locations. Plasmid-mediated resistance to penicillin was found in 28 (14-6%) strains and was associated predominantly with the presence of 5 0 kb penicillinase encoding plasmid (18/28, 64 %). Chromosomal resistance to penicillin (MIC ) 1 mg/l) was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Both 3.2 MDa and 4.4 MDa b-lactamase plasmids are present on the African continent. Unlike South Africa where the 4.4 MDa plasmid is predominant, the majority of PPNG in all other countries carry the 3.2 MDa plasmid, which was also the case in this study 5,6,8,10,21 .…”
Section: Discussionsupporting
confidence: 62%
“…Both 3.2 MDa and 4.4 MDa b-lactamase plasmids are present on the African continent. Unlike South Africa where the 4.4 MDa plasmid is predominant, the majority of PPNG in all other countries carry the 3.2 MDa plasmid, which was also the case in this study 5,6,8,10,21 .…”
Section: Discussionsupporting
confidence: 62%
“…6 15 30 31 In contrast, no TRNG were detected during 1990-3 in a study of isolates made from symptomatic men conducted in Durban, South Africa, 32 or in Carltonville, South Africa between 1989 and 1990. 33 In most studies few data exist about the genetic basis of the resistance other than plasmid size, although in isolates from Zaire the presence of tetM was confirmed by DNA hybridisation and the plasmid was demonstrated to be of the American type. 6 In the present study, travellers visiting Kenya and Nigeria contributed most (29/60) of the TRNG infections originating in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Over a 10 year period, the proportion of isolates of N gonorrhoeae producing ,B-lactamase has increased from < 1 % to 13% in Johannesburg7081 82; in Durban, PPNG was reported in more than 25% of gonococcal isolates recovered in the late 1980s. "1 1867 Trends in other centres such as Pretoria, Carletonville, Cape Town, Port Elizabeth, and Bloemfontein appear to lag those of Johannesburg and Durban by several years, but the relative prevalence of PPNG still continues to rise656971 778284 86 In addition, emerging chromosomal resistance to ,B-lactam antibiotics in non-PPNG strains is also being documented.7085 As compounding evidence made clear that penicillin would no longer be the treatment of choice for gonorrhoea, other antibiotics such as tetracycline, spectinomycin, and cephalosporins were recommended. In 1991, however, a study reported that 56% of PPNG strains and 34% of non-PPNG strains isolated in Johannesburg were now resistant to tetracycline.…”
Section: Non-ulcerative Infections Gonococcal Infectionsmentioning
confidence: 99%